THE IMPLEMENTATION OF REGIONAL REGULATION EMPOWERMENT OF STREET VENDORS IN THE CENTRAL MARKET IN THE GORONTALO CITY - Mahmud, Syamsiar I.; Sulila, Ismet (Journal of Community Research and Service, 2020)
The research aimed: (1) to determine the implementation of regional regulation Number 2 of 2017 concerning the arrangement and empowerment of street vendors reviewed from: data collection of street vendors, empowerment of street vendors, as well as monitoring and evaluation of street vendors. (2) to find out the determination of the implementation of regional regulation Number 2 of 2017 reviewed from: communication, human resources, disposition, and bureaucratic structure. It applied a descriptive research method, and the research site was at Pasar Sentral of Gorontalo City. Data collection techniques were observation, interview, and documentation, which were further analyzed using qualitative data based on Miles and Huberman concept. The research finding revealed that the implementation of local regulation Number 2 of 2017 concerning the arrangement and empowerment of street vendors reviewed from data collection, empowerment, monitoring, and evaluation had not been optimal. From the data collection aspect regarding business legality was not in accordance with regional regulation, the empowerment of street vendors only covered the granting of access to business places and capital, and the assistance and supervision, which were the rights and obligations of street vendors were not implemented. Therefore, in dealing with those problems, then the determinant factor of the implementation of regional regulation number 2 of 2017 based on the theory of Edwards III reviewed from communication, human resources, disposition, bureaucratic structure, and community support also had not been implemented properly. From the human resources aspect,the engineering department had an employee shortage, while the disposition which was performed by the department had obstacles from the target group (street vendors), as well as lack of support from the community.  Keywords: Arrangement; Empowerment; Street Vendors.